Toward a Tailored Acoustic-Based Approach in Music Neuromodulation in Epilepsy - Strýček, Ondřej; Mekyska, Jiří; Miklánek, Štěpán; Fusek, Michal; Štillová, Klára; Mazánek, Martin; Rektor, Ivan (My University, 2025)
Background Music-based neuromodulation has garnered interest as a potential therapeutic approach for drug-resistant epilepsy. This study expands on prior research by examining the effects of different musical features on interictal epileptiform discharges (IEDs) within intracerebral EEG (iEEG). Methods Twenty-five patients with drug-resistant epilepsy undergoing presurgical iEEG evaluation participated in the study. Over 2days, patients listened to various musical compositions characterized by distinct acoustic properties. EEG measurements were recorded before and after each listening session to evaluate IED changes. Results The study identified individualized patterns in IED reduction, with certain acoustic properties showing consistent effects across musical genres. Mozart's “Piano Concerto No. 27” K 595c globally reduced IEDs by 28% while listening to music (p=0.0191) and 19% in the postmusic resting state (p=0.0111); relaxation music increased IEDs by 55% (p=0.0197). Based on the acoustic analysis of individuals, we identified compositions that significantly reduced IEDs, with reductions ranging from 32% to 44% (p=0.0001). In contrast, compositions with differing acoustic properties did not result in significant changes in IEDs. These results suggest that specific acoustic properties, rather than genre, primarily influence IEDs. Conclusions The findings suggest that specific acoustic properties can influence brain activity in a reproducible manner at the individual level, modulating IEDs based on personalized testing and selection across a spectrum of musical genres. These results suggest the potential for music-based neuromodulation as a personalized therapeutic approach in epilepsy management, emphasizing the importance of acoustic features over musical genre. Further research is needed to explore individual aspects of music-based interventions.

Background Music-based neuromodulation has garnered interest as a potential therapeutic approach for drug-resistant epilepsy. This study expands on prior research by examining the effects of different musical features on interictal epileptiform discharges (IEDs) within intracerebral EEG (iEEG). Methods Twenty-five patients with drug-resistant epilepsy undergoing presurgical iEEG evaluation participated in the study. Over 2days, patients listened to various musical compositions characterized by distinct acoustic properties. EEG measurements were recorded before and after each listening session to evaluate IED changes. Results The study identified individualized patterns in IED reduction, with certain acoustic properties showing consistent effects across musical genres. Mozart's “Piano Concerto No. 27” K 595c globally reduced IEDs by 28% while listening to music (p=0.0191) and 19% in the postmusic resting state (p=0.0111); relaxation music increased IEDs by 55% (p=0.0197). Based on the acoustic analysis of individuals, we identified compositions that significantly reduced IEDs, with reductions ranging from 32% to 44% (p=0.0001). In contrast, compositions with differing acoustic properties did not result in significant changes in IEDs. These results suggest that specific acoustic properties, rather than genre, primarily influence IEDs. Conclusions The findings suggest that specific acoustic properties can influence brain activity in a reproducible manner at the individual level, modulating IEDs based on personalized testing and selection across a spectrum of musical genres. These results suggest the potential for music-based neuromodulation as a personalized therapeutic approach in epilepsy management, emphasizing the importance of acoustic features over musical genre. Further research is needed to explore individual aspects of music-based interventions.
Toward a Tailored Acoustic-Based Approach in Music Neuromodulation in Epilepsy
Keywords: acoustic properties; epilepsy; iEEG; interictal epileptiform discharges; music; acoustic properties; epilepsy; iEEG; interictal epileptiform discharges; music